Consequences of bias-motivated victimisation among Swedish university students with an immigrant or minority background. Issue 2 (August 2016) - Andersson, Mika; Mellgren, Caroline
The present article examines the impact of racist and xenophobic victimisation among students with a minority and/or immigrant background in a Swedish context. We examine if racist and/or xenophobic victimisation result in 1) behavioral strategies applied to reduce victimisation risk, 2) a heightened level of fear and 3) if the motive in itself has an independent effect on the level of fear among victims. The study design combines survey data with interviews. The findings suggest that experiences of racist and/or xenophobic victimisation lead to higher levels of fear and that the motive in itself influences this relationship independently. We also found that certain behavioural strategies are developed in order to avoid victimisation.